2011
DOI: 10.1080/10941665.2011.588869
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Hotels to Increasing Food Costs due to Food Shortages

Abstract: the hotel industry in Hong Kong had to respond to a steady price increase in general food items and in basic food commodities. As most hotels in Hong Kong predict their food cost budgets a year in advance, these sudden and unexpected increases in food commodities came at a time when there was a downturn in the global economy in the wake of the financial crisis and a worldwide influenza A (H1N1) epidemic. There have been articles published in hospitality and tourism journals that have discussed the issue of foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Inventory control with menu changes seemed to have been a challenge at both locations. As mentioned by Gunders (2012), stock levels are challenging to manage when demand is unpredictable, particularly for new menu items; therefore, inventories were constantly in flux (Fine, 2009;Mackenzie et al, 2011;Kling, 1943;Youngs et al, 1983). The conventional approach to stock control in the two facilities was a "bottom up" process where stockholding charges are balanced against clerical purchasing costs for individual items or perhaps groups of items, given that the two restaurants were franchises and part of a purchasing group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inventory control with menu changes seemed to have been a challenge at both locations. As mentioned by Gunders (2012), stock levels are challenging to manage when demand is unpredictable, particularly for new menu items; therefore, inventories were constantly in flux (Fine, 2009;Mackenzie et al, 2011;Kling, 1943;Youngs et al, 1983). The conventional approach to stock control in the two facilities was a "bottom up" process where stockholding charges are balanced against clerical purchasing costs for individual items or perhaps groups of items, given that the two restaurants were franchises and part of a purchasing group.…”
Section: Discussionmentioning
confidence: 99%
“…Weather, local events, chronic disruptions like jobsites and holidays may unexpectedly impact the demand for food (Gunders, 2012). With unexpected fluctuations in customers, prepared food may spoil before being eaten (Mackenzie et al, 2011), making inventory prediction and control difficult.…”
Section: Inventory and Demand Managementmentioning
confidence: 99%
“…• Working sustainably is ethical, and it is the right thing to do. As resources become scarce and food security becomes an issue, this will be the only way to operate (Mackenzie et al, 2011).…”
Section: Justificationmentioning
confidence: 99%
“…After the design of the factors, an item pool is created which constitutes the content of each factor. Both in designing the factors related to the causes of food waste and in determining the items that constitute these factors, different studies in the literature (Rolls et al, 1981;Buzby and Guthrie, 2002;Wansink, 2004;Ledikwe, Ello-Martin, & Rolls, 2005;Niemeier, 2005;Rozin, 2005;Quested and Johnson, 2009;Wansink, 2009;Parfitt, Barthel and Macnaughton, 2010;Gustavsson, et al, 2011;Mackenzie et al, 2011;Gunders, 2012;Marthinsen et al, 2012;Saad, 2012;Gjerris and Gaiani, 2013;Kallbekken and Saelen, 2013;Lipinski et al, 2013;Quested, Marsh, Stunell and Parry, 2013;WRAP, 2013;Buzby, Wells and Hyman, 2014;Dölekoğlu et al, 2014;Pirani and Arafat, 2014;Omidiani and Hashemi Hezaveh, 2016;Thyberg and Tonjes, 2016) analyses of the scheme, it is concluded that the scale is most efficient with 29 items and five factors. After various analyzes to achieve the requirements such as reliability, validity and internal consistency, the final draft of FWAS scale has Cronbach's Alpha coefficient () of 0,944 (>0,70), and the total variance explained value of five factors is 63,68 (>0,50).…”
Section: Methodsmentioning
confidence: 99%